Patient satisfaction and visual function after pseudophakic monovision - Finkelman, Y.; Ng, Jonathon; Barrett, G. (Elsevier BV, 2009)
Purpose: To evaluate the visual outcomes and patient satisfaction with modified pseudophakic monovision. Setting: Tertiary teaching hospital. Methods: This prospective study comprised patients with emmetropia after first-eye cataract surgery who were offered monovision for the second-eye surgery with a moderate myopic target refraction (-1.00 to -1.50 diopters [D]). Visual acuity, contrast sensitivity, stereopsis, patient satisfaction, and degree of spectacle independence were measured preoperatively and 3 to 4 months postoperatively. Results: The study evaluated 52 eyes of 26 patients with a mean anisometropia between the near eye and the distance eye of 1.16 D. Uncorrected distance visual acuity was at least 20/30 in 96% of patients, with 92% achieving N8 (J4) or better uncorrected near acuity. Good stereopsis and contrast sensitivity were maintained. Patients were generally satisfied with the surgery. One fourth of patients were completely independent of spectacles; 1 patient was totally dependent on spectacles. No patient required intraocular lens (IOL) exchange or other refractive corrective procedures. Conclusion: Monovision with modest refractive targets achieved good visual function and patient satisfaction without the inherent risk for troublesome visual symptoms associated with multifocal IOLs. © 2009 ASCRS and ESCRS.